ASPECTOS HIDROGEOLÓGICOS EN EL SITIO DEL EMBALSE CIPRESES, P.H. CARIBLANCO Y APLICACIÓN DE TRAZADORES EN AGUA SUBTERRÁNEA - Vargas, Asdrúbal (2011)
The hydrogeological conditions in an area between Cariblanco and San Miguel of Sarapiquí onthe northeastern slope of Cerro Congo was investigated. The area is characterized by volcanic rocks and highprecipitation values. Some lava flows have moderate permeability and generate important springs; for example,the spring San Miguel with a discharge greater than 300 l/s. Near to the spring the Instituto Costarricense deElectricidad (ICE) has planned to built a reservoir and a dike for the Cariblanco hydroelectric project. The objec-tive of this work is to evaluate the incidence of the excavation over the spring San Miguel.Two water table aquifers and a confined aquifer exist in the study area. The upper water table aquifer is formedby fractured lavas and the groundwater flows to the surface mainly through the San Miguel spring. By usinghydrochemical analysis, geological core information and artificial tracer injected in groundwater the absence ofthe water table aquifer in the reservoir area was defined and the construction of the water reservoir probably hasno influence on the discharge and water quality of the San Miguel spring. Artificial tracers can be used to sim-ulate the flow and transport of contaminant and to calculate the mechanical dispersion coefficient of somesolutes in the groundwater.